Insufficient Vitamin C Levels among Adults in the United States: Results from the NHANES Surveys, 2003–2006 - Jennifer Crook (MDPI AG, 2021)
Vitamin C, well-established in immune function and a key factor in epigenetic inflammatory modifications, is only obtained through consistent dietary intake. Identifying individuals at risk for Vitamin C insufficiency may guide prevention and treatment, however, national surveillance has not been evaluated in the United States since 2006. A descriptive, cross-sectional secondary analysis was performed utilizing data from the 2003–2006 National Health and Nutrition Examination Surveys (NHANES) assessing non-institutionalized adults. Five categories of plasma Vitamin C were delineated: deficiency (<11 μmol/L), hypovitaminosis (11–23 μmol/L), inadequate (23–49 μmol/L), adequate (50–69 μmol/L), and saturating (≥70 μmol/L). Results indicated 41.8% of the population possessed insufficient levels (deficiency, hypovitaminosis, and inadequate) of Vitamin C. Males, adults aged 20–59, Black and Mexican Americans, smokers, individuals with increased BMI, middle and high poverty to income ratio and food insecurity were significantly associated with insufficient Vitamin C plasma levels. Plasma Vitamin C levels reveal a large proportion of the population still at risk for inflammatory driven disease with little to no symptoms of Vitamin C hypovitaminosis. Recognition and regulation of the health impact of Vitamin C support the goal of Nutrition and Healthy Eating as part of the Healthy People 2030.